Validation of the FLUKA code to simulate response functions of organic liquid scintillator for high‐energy neutrons - Ahad Ghavami; Mojtaba Tajik (Nuclear Engineering and Technology)
In this research, the FLUKA code was employed to calculate the response functions of the BC501A organic scintillation detector for energies ranging from 25 to 800 MeV. Using the AUXSCORE, EVENTBIN and TCQUENCH cards, the response function of the BC501A organic scintillation detector to mono-energetic neutrons in the energy range of 25–800 MeV was computed. The comparison confirms that the simulation results obtained from the FLUKA code show a promising agreement with the results obtained from experiments, other codes, and the analytical method.